Impact of Delay of Treatment With Disease‐Modifying Antirheumatic Drugs in Psoriatic Arthritis: The CorEvitas Psoriatic Arthritis/Spondyloarthritis Registry - Philip J. Mease; Miroslawa Nowak; Jiyoon Choi; Thomas Lehman; Antoine Sreih; Kaylee Ho; Nicole Middaugh; Alexis Ogdie (ACR Open Rheumatology)
Objective Our objective was to describe characteristics and compare clinical and patient‐reported outcomes (PROs) for disease‐modifying antirheumatic drug (DMARD)–naive patients with psoriatic arthritis (PsA) who initiate DMARD therapy early versus late. Methods Patients with PsA from the CorEvitas PsA/Spondyloarthritis Registry were classified by reported time between diagnosis and DMARD initiation. Early and late initiators were patients whose first DMARD treatment occurred ≤1 year or >1 year, respectively, following PsA diagnosis. Change in disease activity and PRO measures from initiation to the six‐month follow‐up was calculated for each group; mean change for each continuous outcome and proportion achieving binary outcomes were reported for early and late initiators. Associations of early versus late DMARD initiation with disease activity and PROs at six months were calculated using adjusted linear and Poisson regressions. Results The mean patient age was 53 years, more than half of patients were female, and 90% of patients were White. Mean time from diagnosis to DMARD initiation was 0.2 years in early initiators (n = 229, 79%) and 8.6 years in late initiators (n = 62, 21%). In adjusted analyses, achievement of minimal disease activity (adjusted risk ratio 2.01, 95% confidence interval [CI] 1.03–4.40) and mean change in Clinical Disease Activity Index (β −3.4, 95% CI −6.2 to −0.49) were statistically different between early and late initiators. Conclusion Among patients from the PsA registry, those who had both early and late initiation of DMARD therapy experienced improvements throughout all disease activity and PROs across six months of treatment. Minimal disease activity, a key treatment target, was more likely observed in early initiators, highlighting the value of early identification and treatment. Impact of Delay of Treatment With Disease‐Modifying Antirheumatic Drugs in Psoriatic Arthritis: The CorEvitas Psoriatic Arthritis/Spondyloarthritis Registry [Correction added on 16 July 2025, after first online publication: The graphical abstract image title has been updated.]